A influência da declividade do terreno e do tempo de experiência dos operadores no rendimento do feller buncher - Miyajima, Ricardo Hideaki [UNESP]; Tonin, Rodrigo Petrongari [UNESP]; De Souza Passos, José Raimundo [UNESP]; Fenner, Paulo Torres [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
Terrain slope and operators time of experience significantly affect yield and, consequently, wood harvesting costs, which is one of the most costly activities of productive chain of planted forests. A full tree harvesting system was studied by comparing the performance of feller buncher according to the direction of slope and operators time of experience. A clonal eucalyptus forest was studied with a planting spacing of 3.00 m x 2.00 m and the forest was six years old at harvesting time. Data were obtained through a study of times and yields, by the continuous time method. Determined were yield, operational efficiency and the effective average cycle time. The average yield of feller buncher decreased with the increase of the terrain slope. On average, the yield was 124.92 m3 h-1 for the wavy slope and was 142.00 m3 h-1 for the flat slope. Yield was greater when comparing flat slope to wavy slope; it was 16.60% for the operator 2 and 19.93% for the operator 3. Regardless of the operators time of experience the yield was higher on the flat terrain when compared to wavy terrain. Regardless of terrain slope yield increased with increasing operator's time of experience. In flat slope the operational efficiency was higher when compared to the wavy one. Partial activity cutting was the most time consuming, followed by empty turning and tilting.
Terrain slope and operators experience time influence on feller buncher yield
Keywords: Eucalyptus; Harvesting; Planning; Time and yields; Yield